2022
DOI: 10.1186/s12870-022-03897-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated mitochondrial biogenesis and cell death competence in maize pollen

Abstract: Background Cytoplasmic male sterility (CMS) is a maternally inherited failure to produce functional pollen that most commonly results from expression of novel, chimeric mitochondrial genes. In Zea mays, cytoplasmic male sterility type S (CMS-S) is characterized by the collapse of immature, bi-cellular pollen. Molecular and cellular features of developing CMS-S and normal (N) cytoplasm pollen were compared to determine the role of mitochondria in these differing developmental fates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
1
3
0
Order By: Relevance
“…In addition, the upregulation of alternative oxidase (AOX) expression may be caused by the inhibition of cytochrome pathway, this is consistent with Karen's research [97]. Previous studies have shown that defects in the TCA cycle may also lead to producing excessive amounts of ROS.…”
Section: Possible Transcriptome-mediated Male Sterility Network In K-...supporting
confidence: 85%
“…In addition, the upregulation of alternative oxidase (AOX) expression may be caused by the inhibition of cytochrome pathway, this is consistent with Karen's research [97]. Previous studies have shown that defects in the TCA cycle may also lead to producing excessive amounts of ROS.…”
Section: Possible Transcriptome-mediated Male Sterility Network In K-...supporting
confidence: 85%
“…However, the coincidence between the heterogeneity of mitochondria volumes with the pollen death heterogenous timing leads us to hypothesize that mitochondria swelling likely reflects a late phase in the process of pollen abortion. No mitochondria swelling in pollen was reported in the gametophytic S-CMS of maize after mitochondria-targeted GFP imaging (Chamusco et al, 2022), and mitochondrial morphology was not described in the HL-CMS of rice, to our knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…However, the coincidence between the heterogeneity of mitochondria volumes with the pollen death heterogenous timing leads us to hypothesize that mitochondria swelling likely reflects a late phase in the process of pollen abortion. No mitochondria swelling in pollen was reported in the gametophytic S-CMS of maize after mitochondria-targeted GFP imaging (Chamusco et al ., 2022), and mitochondrial morphology was not described in the HL-CMS of rice, to our knowledge. However, changes in mitochondrial morphology were reported from electron microscopy observations in the tapetal cells of sporophytic sunflower PET1-CMS (Horner, 1977), rapeseed Ogura CMS (González-Melendi et al ., 2008), soybean CMS (Smith et al ., 2002), and of thermosensitive genic-male sterility of rice (Ku et al ., 2003) and in pollen tubes experiencing the Papaver rhoeas self-incompatibility response (Geitmann et al ., 2004), supporting the view that it is a convergent step in diverse cell death processes.…”
Section: Discussionmentioning
confidence: 99%
“…roGFP‐based biosensors are effective tools for exploring redox dynamics in subcellular compartments at high spatiotemporal resolution in plants (Bratt et al., 2016; Gutscher et al., 2008; Jiang et al., 2006; Lampl et al., 2022; Meyer, 2008; Meyer & Dick, 2010; Nietzel et al., 2019; Schwarzländer et al., 2016; Ugalde et al., 2021; Ugalde et al., 2022). Genetically encoded biosensors have also been introduced into crop plants, including potato (Chamusco et al., 2022; Hipsch et al., 2021; Huang et al., 2014; Rattanawong et al., 2021), and spatially resolved mapping of stress‐induced long‐term redox perturbations has recently been demonstrated by whole‐plant imaging of potato plants expressing roGFP2 in their chloroplasts (Hipsch et al., 2021). Additionally, in potato plants infected with the potato virus Y, chloroplast‐targeted roGFP2 has been used to demonstrate the role of chloroplast redox state in SA‐independent cell death signaling and SA‐dependent HR (Lukan et al., 2023).…”
Section: Introductionmentioning
confidence: 99%